THE ADVANTAGES AND DISADVANTAGES OF SYNDROMIC SURVEILLANCE METHODS - Sukada, I Made; Kardena, I Made (Buletin Veteriner Udayana, 2012)
Syndromic surveillance is surveillance methods which has the potential to detect diseasesoutbreak in the early stages. The systems used existing data of disease syndromes whichgenerally appear at the beginning of infection to provide immediate analysis. Additionally,the method may identify the disease outbreak earlier than the conventional surveillancewhich commonly requires a longer time to determine the cause of the outbreaks. Althoughmany experts believe that syndromic surveillance is a good method for early detection ofdisease outbreak, some of them also believe that this system has several drawbacks
Keywords: syndromic surveillance, early detection system, animal health system